'[T]his is eating your greens, this is doing your homework': writing and rehearsing a full-length stand-up show. Issue 2 (3rd July 2017) - Double, Oliver
ABSTRACT: Until recently, the processes which comedians use to create their performances have been seldom examined. This article draws on materials from the British Stand-Up Comedy Archive (BSUCA) and a recent practice-as-research project in which I documented the creative processes behind my full-length stand-up show Break a Leg, performed at the Gulbenkian Theatre, Canterbury in 2015. In the months leading up to the show, I regularly recorded my reflections on the creative processes in which I was engaged, publishing these in the podcast Breaking a Leg, which is available on iTunes. Using these reflections in conjunction with script notes, set lists and unpublished recordings from the BSUCA, this article articulates what Robin Nelson calls 'know-what' – the performer's tacit, experiential knowledge made explicit through critical reflection – to shed light on the processes of writing, structuring and rehearsing stand-up comedy. Matthew Reason has argued that the main motivation for documenting live performance is 'not the creation of new art but ensuring the documentation of existing art'. Building on recent work by Christopher Molineux, here I argue that this is not the case with stand-up comedy, where the purpose of documentation is very much the creation of new art.